LOOKING AT THE MODEL OF "PERSONAL BRANDING" OF PROPHET YUSUF ‘ALAIHISSALAM IN THE QUR'AN BASED ON PETER MONTOYA'S PERSPECTIVE: SEMANTIC ANALYSIS STUDY - Maftukhah, Nuriatul; Ma'ali, Abul (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
Highlighting one's own strengths to the general public both directly and indirectly is often termed personal branding. This term is used to build people's positive perception of personal merit. This has been done by the Prophets, one of which is Prophet Yusuf ‘alaihissalam as the verses in Surat Yusuf. The purpose of this study is to find out the personal branding model according to Peter Montoya's theory conducted by Prophet Yusuf ‘alaihissalam based on Yusuf Verse. Research with this type of qualitative is in the form of library research using content analysis in the form of Surat Yusuf in the Qur'an then analyzed descriptively to obtain conclusions. The results of this study show that Prophet Yusuf ‘alaihissalam brands himself as a dream taker, and a person who is good at keeping again knowledgeable. To strengthen his personal branding, Allah the Exalted shows many advantages including having a handsome face, justifying the results of his supervision, and making people rank in the Egyptian state at that time. The branding carried out by Prophet Yusuf himself and by Allah through His kalam shows according to Peter Montoya's personal branding principles, specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill.